Simulator Charging System Dan Pengaruh Perubahan RPM Terhadap Laju Pengisian Baterai - Darma Aviva; Abdul Halim; Faisyal Faisyal; Baso Cante (MEDIA PERSPEKTIF : Journal of Technology, 2021)
Lack of understanding of students graduating from the Samarinda State Polytechnic Heavy Equipment Engineering Study Program and the availability of facilities in the form of teaching aids that support learning about Electrical Systems, especially Charging Systems at the Samarinda State Polytechnic Heavy Equipment Engineering Workshop. Charging System is a system that converts mechanical energy from the engine into electrical energy to charge the battery and supply electric current to operate the electrical system of a vehicle. When the ignition switch is in the on position and the electric motor is turned on to rotate the alternator, the alternator will carry out its duties in the Charging System and recharge the battery. This teaching aid can explain how the series of components of the Charging System and the working system of the Charging System. The aim of this research is to determine the amount of output supplied by the alternator when it is at a certain RPM with the alternator component belonging to the Caterpillar 390D unit. This teaching aid uses a 24V 95 ampere alternator, 2 HP1 phase AC electric motor, 12V battery, belt and monitor panel as the main components. To support this Charging System props, a stand is used.